Double-Docking Technique for Femtosecond Laser-Assisted Deep Anterior Lamellar Keratoplasty. Issue 1 (January 2018) - Guindolet, Damien; Nguyen, Diem T.; Bergin, Ciara; Doan, Serge; Cochereau, Isabelle; Gabison, Eric E.
Abstract : Purpose: To describe a new and safe surgical technique of deep anterior lamellar keratoplasty (DALK) using the femtosecond laser (FSL) and intraoperative optical coherence tomography (iOCT) for surgical management of corneal thinning and/or opacities. The technique was coined the double-docking procedure for DALK (DD-DALK). Methods: FSL-integrated iOCT was used for direct visualization and calibration to perform precise anterior lamellar and side cuts for the removal of the anterior stroma. Air was then injected in the residual posterior stroma to detach Descemet membrane [big-bubble (BB) formation]. Returning the residual posterior stroma into the docked position, a cylindrical vertical cut was made with the FSL to securely open the BB roof. Next, the stromal roof of the BB was removed with forceps leaving Descemet membrane intact, followed by a lamellar corneal graft. Results: Anterior stroma resection, BB formation, and residual stromal resection were achieved in every case without perforation. The curved applanation surface helped to limit the formation of folds on the posterior stroma (ie, advanced thinning). Conclusions: DD-DALK is a reproducible and safe procedure for surgical management of corneal thinning and/or opacities. The precision of stromal cuts made by the FSL and iOCT guidance for air injection increases success in DD-DALK preparation. Abstract : Supplemental Digital Content is Available in the Text.